The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1088/0268-1242/22/3/012
|View full text |Cite
|
Sign up to set email alerts
|

Double transit region Gunn diodes

Abstract: We report the first epitaxially grown, double transit region Gunn diode oscillator. The prototype device was operated at its second harmonic of 77 GHz, giving an RF output power of 64 mW as compared with 54 mW from the corresponding single transit region device. Measurements of threshold and breakdown voltage and of RF power support the interpretation of coherent nucleation of Gunn domains in the two transit regions and the satisfactory operation of the device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…It is observed that the I-V curves flatten for voltages above a value of around ~3 V in both cases. This behaviour is normally attributed to the occurrence of a significant intervalley scattering in the device channel [6,7,9]. It is also observed that the current is somewhat higher (~15-25%) in the device with all-ohmic contacts, in both the linear and the saturation regimes.…”
Section: Monte Carlo Simulationsmentioning
confidence: 90%
See 1 more Smart Citation
“…It is observed that the I-V curves flatten for voltages above a value of around ~3 V in both cases. This behaviour is normally attributed to the occurrence of a significant intervalley scattering in the device channel [6,7,9]. It is also observed that the current is somewhat higher (~15-25%) in the device with all-ohmic contacts, in both the linear and the saturation regimes.…”
Section: Monte Carlo Simulationsmentioning
confidence: 90%
“…Gunn diodes can generate continuous wave signal with low phase noise in the GHz range, with output powers up to 100 mW [5,6,7]. Thus, they are good candidates for mm-wave and THz emission, provided their operation frequency can be extended into the THz regime.…”
Section: Introductionmentioning
confidence: 99%
“…A well-known electronic source at lower frequencies is the Gunn diode, which is able to produce a pure continuous wave (CW) signal with low phase noise; dependent upon the output frequency and material, powers in the range of ∼10-100 mW are commonly possible [4,5]. The Joule heating in these structures gives rise to their key limitation, since in most cases electron densities much beyond 10 16 cm −3 cause thermal management issues.…”
Section: Introductionmentioning
confidence: 99%